ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA PADA PT. BANK TABUNGAN NEGARA, (PERSERO) TBK. CAB. MANADO - MASWATU, A GHAZALI; PELLENG, FRENDY; Tampi, Dolina (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
ABSTRACT- Sources and uses of working capital determines the success of a banking company. Assessment of working capital in principle lead to; current assets, current liabilities and Working Capital Turnover. The purpose of this study was to determine how the implementation of the analysis of sources and uses of working capital at PT. Bank Tabungan Negara, Tbk, . branch Office of Manado. The method used is descriptive method using a quantitative approach to the analysis of financial statements. Data and datasource is the annual report data from PT. Bank Tabungan Negara Tbk, Limited, Branch Office Manado fiscal year 2013 and 2014. The results showed that: (1) The role of the sources and uses of working capital as a whole, showing the level of effectiveness and efficiency is maintained so the security of the banking financial turnaround can work well and do not affect workers at the PT. Bank Tabungan Negara Tbk. Branch Manado., (2) development of the use of working capital PT. Bank Tabungan Negara, Tbk Branch Manado from years 2013 - 2014 corresponding financial statement analysis had experienced an increase in which the total assets to net working capital ratio shows the change of + 3.87; Current Liabilities to net working capital ratio shows changes + 3.577 and Working Capital Turnover ratio shows the change of + 2.933. Observing the development of resources and the use of working capital at PT. Bank Tabungan Negara Tbk. shows the rate of change increased (+), then it is suggested, that the bank's management constantly review, evaluate and assess reports of capital sources and uses of working capital so that it can ensure the performance of banking services increasingly better in the future.Keywords: Source of Funds, Use of Funds, Working Capital